Nano lithium carbonate and preparation method thereof

By impregnating waste lithium iron phosphate in a mixed solution of acidic solution and oxidizing agent, combined with the steps of removing impurities and adjusting pH of sodium carbonate, nano lithium carbonate with high purity and low impurity content is prepared, which solves the problems of low purity and high impurities in traditional processes, and improves the reproducibility of preparation and the recycling of resources.

CN119797401APending Publication Date: 2025-04-11GREEN IND INNOVATION RES INST OF ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510152547.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the existing lithium carbonate preparation process, the lithium carbonate obtained by the by-product method has low purity, high impurity content, and poor reproducibility.

Method used

Use waste lithium iron phosphate as raw material to prepare nano lithium carbonate through the steps of impregnation of mixed solution of acid solution and oxidant, removal of impurities of calcified substances, adjustment of pH value of sodium carbonate and heating and stirring.

Benefits of technology

The preparation of nano lithium carbonate with high purity and low impurity content has good reaction reproducibility and promotes the recycling of waste lithium iron phosphate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797401A_ABST
    Figure CN119797401A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium carbonate materials, and discloses a preparation method of nano lithium carbonate, which comprises the following steps: dipping waste lithium iron phosphate in a mixed solution of an acid solution and an oxidizing agent to obtain a first suspension, and carrying out solid-liquid separation on the first suspension to obtain a first lithium-rich solution; adding a calcium compound into the first lithium-rich solution until the pH value is 6, continuously heating and stirring to obtain a mixture of ferric hydroxide precipitate and a second turbid liquid, and carrying out solid-liquid separation on the second turbid liquid to obtain a second lithium-rich solution; adjusting the pH value of the second lithium-rich solution to 10-12, adding sodium carbonate, heating and stirring to obtain a third suspension, and carrying out solid-liquid separation on the third suspension to obtain a third lithium-rich solution; and concentrating and washing the third lithium-rich solution to obtain the nano lithium carbonate. According to the method, the waste lithium iron phosphate is used as the raw material to prepare the nanometer lithium carbonate, the microstructure of the nanometer lithium carbonate material can be effectively controlled, and meanwhile recycling of the waste lithium iron phosphate is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium carbonate materials, and in particular to nano lithium carbonate and a preparation method thereof. Background Art

[0002] As the lightest metal, lithium exists in many compounds in nature. As a basic inorganic lithium salt, lithium carbonate has shown extensive application potential and important scientific research value in the fields of materials science and medicine. It is particularly worth mentioning that in the field of lithium-ion batteries, lithium carbonate is a core raw material, and its performance is directly related to the energy density and cycle stability of the battery. In addition, lithium carbonate has also shown significant therapeutic effects in the medical field, especially in the treatment of mania and the improvement of schizophrenia affective disorders, and its efficacy has been widely recognized.

[0003] At present, the traditional preparation process of lithium carbonate is relatively mature, and the by-product method is constantly optimized. However, the lithium carbonate prepared by the by-product method generally has low purity, high impurity content, and poor reproducibility. Therefore, it is urgent to provide a lithium carbonate material with high purity and low impurity content. Summary of the invention

[0004] In view of this, the present invention provides a method for preparing nano lithium carbonate to solve the problem that the lithium carbonate prepared by the existing by-product method has low purity and high impurity content.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a method for preparing nano lithium carbonate, comprising the following steps:

[0007] (1) immersing waste lithium iron phosphate in a mixed solution of an acidic solution and an oxidant to obtain a first suspension, and performing solid-liquid separation on the first suspension to obtain a first lithium-rich solution;

[0008] (2) adding a calcium compound to the first lithium-rich solution until the pH value is 6, continuing heating and stirring to obtain a mixture of iron hydroxide precipitate and a second suspension, and performing solid-liquid separation on the second suspension to obtain a second lithium-rich solution;

[0009] (3) adjusting the pH of the second lithium-rich solution to 10-12, adding sodium carbonate, heating and stirring to obtain a third suspension, and performing solid-liquid separation on the third suspension to obtain a third lithium-rich solution;

[0010] (4) Concentrating and washing the third lithium-rich solution to obtain nano lithium carbonate.

[0011] Preferably, in step (1), the ratio of the waste lithium iron phosphate to the mixed solution is (2-4) g:10 mL.

[0012] Preferably, the volume ratio of the acidic solution to the oxidant is (8-9):1, and the concentration of the acidic solution is 0.6-2 mol / L.

[0013] Preferably, the acidic solution is a strong acid solution, including one or more of sulfuric acid, hydrochloric acid, and nitric acid.

[0014] Preferably, the oxidant includes one or more of hydrogen peroxide, potassium permanganate, and potassium dichromate.

[0015] Preferably, the immersion temperature in step (1) is 50-60° C., and the immersion time is 1-1.5 h.

[0016] Preferably, the mass fraction of the calcification in step (2) is 6-30%.

[0017] Preferably, the calcification includes one or more of calcium carbonate, calcium hydroxide and calcium oxide.

[0018] Preferably, in step (2), after solid-liquid separation of the second suspension, calcium carbonate waste residue is obtained, and the calcium carbonate waste residue is recycled as a calcified product.

[0019] Preferably, step (2) is carried out at 50-60° C., and the heating and stirring time is 25-30 min.

[0020] Preferably, in step (2), after solid-liquid separation of the second suspension, calcium carbonate waste residue is obtained, and the calcium carbonate waste residue is recycled as a calcified product.

[0021] Preferably, the temperature of the heating and stirring in step (3) is 90-110° C., and the time is 25-60 min.

[0022] Preferably, in step (3), the molar amount of calcium ions in the second lithium-rich solution is A, the molar amount of lithium ions in the second lithium-rich solution is B, the amount of sodium carbonate added is C, and A, B, and C satisfy the following condition: C=A+0.5B.

[0023] On the other hand, the present invention also provides a nano-lithium carbonate prepared by any of the preparation methods described above, wherein the nano-lithium carbonate is in a spherical petal shape.

[0024] The present invention provides a nano lithium carbonate, which has the following beneficial effects compared with the prior art:

[0025] The present invention uses waste lithium iron phosphate as a raw material to prepare nano lithium carbonate. The reaction conditions are mild and easy to control, the operation process is simple, and the reaction has good reproducibility. The microscopic morphology of the nano lithium carbonate material can be effectively controlled, and the recycling of waste lithium iron phosphate is realized at the same time.

[0026] The present invention introduces calcium impurity removal technology, which can significantly reduce production costs. The removal rate of iron impurities in waste lithium iron phosphate can reach 99.9%, and the production cost is further reduced by recycling calcium carbonate waste residue.

[0027] The present invention combines precipitation impurity removal technology with crystal growth synthesis technology, giving full play to the advantages of precipitation method in efficiently removing Ca impurities, and also ensures the high purity, particle uniformity and morphology integrity of nano lithium carbonate by accurately controlling the direction of crystal growth.

[0028] The present invention can guide and control the direction of crystal growth by precisely controlling the temperature and solution concentration. Specifically, by finely adjusting the crystallization temperature in steps (3)-(4), the crystal growth rate can be slowed down, thereby facilitating the orderly arrangement and growth of crystals in a specific direction. In addition, by controlling the solutes (including Li + 、Na + , CO 3 2- 、SO 4 2- By controlling key parameters such as the type, concentration, and pH value of the materials (such as ions, etc.), the microenvironment of crystal growth can be precisely regulated, thereby affecting the growth rate and direction of the crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0030] Figure 1 This is a SEM image of nano-lithium carbonate of Examples 1-3 of the present invention;

[0031] Figure 2 This is a SEM image of nano-lithium carbonate of Example 4-6 of the present invention;

[0032] Figure 3 This is the XRD test pattern of the Fe precipitate of the present invention;

[0033] Figure 4 A schematic diagram showing the comparison of the main components of waste lithium iron phosphate LFP-1 and LFP-2;

[0034] Figure 5 It is a comparison chart of Li utilization rate and Fe and Cu removal rate between Example 1 and Example 4;

[0035] Figure 6 The XRD pattern of nano-lithium carbonate of Example 1-6;

[0036] Figure 7 is the infrared spectrum of nano lithium carbonate of Example 1-6;

[0037] Figure 8 This is a comparison chart of the purity of nano lithium carbonate in Examples 1-6;

[0038] Fig. 9 It is a schematic diagram showing the leaching rate of Li and Fe in the waste lithium iron phosphate LFP-1 of Example 1 and Comparative Examples 1-9 as a function of acid concentration;

[0039] Fig.10 It is a schematic diagram showing the utilization rate of Li and the removal rate of Fe in the waste lithium iron phosphate LFP-1 of Example 1 and Comparative Examples 10-17 as a function of pH value;

[0040] Fig.11 Schematic diagram of the changes in Li and Fe concentrations in nano-lithium carbonates in Example 1 and Comparative Examples 18-26 as a function of heating and stirring time;

[0041] Fig.12 It is a schematic diagram showing the Li utilization rate and Fe removal rate in the waste lithium iron phosphate LFP-1 of Example 1 and Comparative Examples 27-38 as a function of reaction temperature;

[0042] Fig.13 The utilization rate of Li and the removal rate of Fe in waste lithium iron phosphate LFP-1 are compared with the increase of CaCO 3 Schematic diagram of the change in emulsion concentration;

[0043] Fig.14 This is a schematic diagram of the effect of multiple recycling of calcium carbonate waste residue;

[0044] Fig.15 This is the XRD spectrum of calcium carbonate waste after multiple recycling. DETAILED DESCRIPTION

[0045] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0046] In one aspect of the present invention, the present invention provides a method for preparing nano lithium carbonate, comprising the following steps:

[0047] (1) The waste lithium iron phosphate is immersed in a mixed solution of an acidic solution and an oxidant to obtain a first suspension, and the first suspension is subjected to solid-liquid separation to obtain an acid leaching solution, i.e., a first lithium-rich solution.

[0048] In some embodiments of the present invention, the ratio of waste lithium iron phosphate and the mixed solution, that is, the solid-liquid ratio, is (2-4) g:10 mL, for example, it can be 2 g:10 mL, 2.5 g:10 mL, 3 g:10 mL, 3.5 g:10 mL, 4 g:10 mL, etc.

[0049] In some embodiments of the present invention, the volume ratio of the acidic solution to the oxidant is (8-9):1, for example, it can be 8:1, 8.5:1, 9:1; wherein, the concentration of the acidic solution is 0.6-2mol / L, for example, it can be 0.6mol / L, 0.8mol / L, 1mol / L, 1.5mol / L, 2mol / L, etc.; the acidic solution is a strong acid solution, including one or more of sulfuric acid, hydrochloric acid, and nitric acid, and its strong acidity can effectively promote the release of lithium ions in lithium iron phosphate; the oxidant includes one or more of hydrogen peroxide, potassium permanganate, and potassium dichromate, and the oxidant significantly optimizes the leaching efficiency of lithium ions by oxidizing ferrous ions to ferric ions.

[0050] In some embodiments of the present invention, the immersion temperature is 50-60°C, for example, 50°C, 55°C, 60°C, etc., and the immersion time is 1-1.5h, for example, 1h, 1.2h, 1.5h, etc.; the solid-liquid separation can be suction filtration or centrifugation, specifically, suction filtration can be performed using a Buchner funnel or centrifugation can be performed using a centrifuge, and there is no special limitation on this.

[0051] The present invention utilizes the selective leaching principle of lithium iron phosphate acid leaching method, utilizes the chemical bonding between lithium ions and phosphate ions in the lithium iron phosphate lattice, and realizes high selectivity of lithium ion leaching through acidic solution and oxidant. Specifically, under acidic conditions, the lattice structure of lithium iron phosphate is disturbed, and the oxidant promotes the transformation of ferrous ions to ferric ions. This transformation not only changes the original chemical state of lithium iron phosphate, but also creates more favorable conditions for its reaction with acid, successfully realizes efficient leaching of lithium ions, and effectively inhibits the leaching of iron and other impurity elements, ensuring the high purity of the product.

[0052] (2) adding calcium to the first lithium-rich solution until the pH value is 6, continuing heating and stirring to obtain a mixture of iron hydroxide precipitate and a second suspension, and performing solid-liquid separation on the second suspension to obtain a second lithium-rich solution.

[0053] In some embodiments of the present invention, step (2) is carried out at 50-60°C, the same as the immersion temperature of step (1), the heating and stirring time is 25-30min, and the rotation speed is 200mL / min, so that the iron ions are fully precipitated.

[0054] In some embodiments of the present invention, the calcification includes one or more of calcium carbonate, calcium hydroxide, and calcium oxide, and the calcification is used as an impurity remover to remove impurities such as iron ions in the first lithium-rich solution. The calcification is added to the first lithium-rich solution in the form of a calcification emulsion, and the dripping speed can be, for example, 10 mL / min, 15 mL / min, 20 mL / min, etc. The mass fraction of the calcification is 6-30%, specifically the amount of the calcification added to the first lithium-rich solution. When the calcification is calcium carbonate, the mass fraction of the calcification is 20-30%, for example, 20%, 25%, 30%, etc.; when the calcification is calcium hydroxide, the mass fraction of the calcification is 6-10%, for example, 6%, 8%, 10%, etc.; when the calcification is calcium oxide, the mass fraction of the calcification is 6.5-7.5%, for example, 6.5%, 7%, 7.5%, etc.

[0055] In some embodiments of the present invention, the solid-liquid separation can be suction filtration or centrifugation, and specifically, suction filtration can be performed using a Buchner funnel or centrifugation can be performed using a centrifuge, and there is no particular limitation on this. Preferably, after the second suspension is subjected to solid-liquid separation, calcium carbonate waste residue is obtained, and the calcium carbonate waste residue can be recycled as an impurity remover.

[0056] Specifically, taking calcium carbonate as an example, calcium carbonate first reacts with the acid in the first lithium-rich solution. This process not only consumes the hydrogen ions in the first lithium-rich solution and reduces the acidity of the solution, but also generates corresponding calcium salts and carbon dioxide gas. Subsequently, with the continuous introduction of carbonate ions (which can be achieved by controlling the amount of calcium carbonate added and the reaction conditions), CO 3 2- Hydrolysis occurs in water to generate OH - ions, these OH - ions and then react with Fe 3+ Reacts to form insoluble Fe(OH) 3 Precipitation; through subsequent solid-liquid separation, the iron hydroxide precipitate can be effectively removed from the solution, thereby achieving efficient impurity removal of iron ions. The present invention not only cleverly utilizes the chemical properties of calcium carbonate, but also ensures the selectivity and efficiency of the impurity removal process by accurately controlling the reaction conditions, thereby improving the purity and impurity removal efficiency of the product.

[0057] like Figure 3 As shown, it is CaCO 3 When removing impurities, the XRD test spectrum of the Fe precipitate shows that the precipitate obtained is a crystalline product. After calcination, Fe 2 O 3 , indicating that the precipitate is Fe(OH) 3 .

[0058] In addition, the impurity removal principle of calcium hydroxide and calcium oxide is similar to that of calcium carbonate, both involving reaction with the acid in the first lithium-rich solution and subsequent hydrolysis or dissolution process. Among them, calcium hydroxide can directly provide hydroxide ions and react with iron ions to form iron hydroxide precipitate; while calcium oxide generates calcium hydroxide after reacting with water, thereby playing a role in impurity removal.

[0059] (3) adjusting the pH of the second lithium-rich solution to 10-12, adding sodium carbonate, heating and stirring to obtain a third suspension, and performing solid-liquid separation on the third suspension to obtain a third lithium-rich solution;

[0060] In some embodiments of the present invention, the temperature of the heating and stirring in step (3) is 90-110°C, and the time is 25-60min. Specifically, first, the temperature is kept constant at 110°C until crystals are precipitated, then the temperature is reduced to 100°C and the temperature is kept constant until a large amount of crystals are precipitated, and finally the temperature is reduced to 90°C and the temperature is kept constant until the water is completely evaporated. The present invention applies temperature gradient crystallization technology during the heating and stirring process. By constructing a specific temperature gradient field in the crystallization system, the grains are guided by the directional growth force under the action of the temperature difference, which effectively suppresses the random growth of the grains and ensures the high-quality growth of the crystals along the preset direction.

[0061] Preferably, the second lithium-rich solution is adjusted to a pH value of 10, 11, 12, etc. by adding an alkaline solution such as sodium hydroxide or potassium hydroxide.

[0062] In some embodiments of the present invention, the amount of sodium carbonate added in step (3) is calculated based on the concentrations of lithium ions and calcium ions in the second lithium-rich solution, and the concentrations of lithium ions and calcium ions in the second lithium-rich solution are measured using atomic absorption spectrometry. Specifically, if the molar amount of calcium ions in the second lithium-rich solution is measured to be A and the molar amount of lithium ions is measured to be B, then the amount of sodium carbonate added is C=A+0.5B.

[0063] In some embodiments of the present invention, the solid-liquid separation can be suction filtration or centrifugation. Specifically, suction filtration can be performed using a Buchner funnel or centrifugation can be performed using a centrifuge. There is no particular limitation on this. The cations in the third lithium-rich solution obtained after solid-liquid separation are only lithium ions.

[0064] In this step, the calcium ion impurities in the second lithium-rich solution react chemically with the added carbonate ions under the above temperature conditions to generate calcium carbonate precipitates; in this process, the change in temperature has a significant effect on the formation and growth of the precipitate. As the temperature rises, the thermal motion of the molecules in the solution intensifies and the collision frequency increases, thereby accelerating the formation and growth rate of the calcium carbonate nuclei, allowing the precipitation reaction to proceed rapidly. This kinetic effect not only significantly shortens the impurity removal cycle, but also effectively improves the precipitation yield, ensures the efficient removal of calcium ion impurities, and effectively avoids the occurrence of side reactions, thereby improving the selectivity of the impurity removal process and the purity of the product.

[0065] (4) Concentrating and washing the third lithium-rich solution to obtain nano lithium carbonate.

[0066] In some embodiments of the present invention, the concentration may be carried out by evaporation concentration at 90-110° C., and the crystals obtained after evaporation concentration are washed with hot water at 100° C. to obtain high-purity nano lithium carbonate.

[0067] In another aspect of the present invention, the present invention provides a nano lithium carbonate, the nano lithium carbonate is in the shape of spherical petals, and the nano lithium carbonate is prepared by the method described above. From the perspective of energy storage, high-purity spherical petal-shaped nano lithium carbonate with uniform size and regular morphology is conducive to improving the electrochemical energy of energy storage devices, so the material can be applied to the lithium ion battery industry and can show excellent energy storage performance.

[0068] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0069] Example 1

[0070] This embodiment provides a method for preparing nano lithium carbonate, and the specific steps are as follows:

[0071] (1) 30 g of waste lithium iron phosphate LFP-1, 90 mL of 1 mol / L sulfuric acid and 10 mL of H 2 O 2 The mixture was stirred and mixed thoroughly, and the mixture was reacted at 60°C for 1 hour to obtain a first suspension. The first suspension was filtered to obtain a Fe-containing 3+ a first lithium-rich solution of impurities;

[0072] (2) At 60°C, add 20% CaCO 3 , CaCO 3 Add dropwise at a dropping speed of 15 mL / min in the form of an emulsion, stop adding dropwise when the pH reaches 6, continue heating and stirring for 30 min, and obtain a mixture of iron hydroxide precipitate and the second suspension;

[0073] (3) filtering the second suspension to obtain a second lithium-rich solution and calcium carbonate waste residue, and collecting the calcium carbonate waste residue for recycling as an impurity remover;

[0074] (4) Using atomic absorption to measure the Li in the second lithium-rich solution + The concentration is 1210mg / L, Ca 2+ The concentration of the second lithium-rich solution is 600 mg / L, and the amount of sodium carbonate to be added is calculated; the pH value of the second lithium-rich solution is adjusted to 10 with NaOH solution, and then sodium carbonate is added. The solution is stirred at 100°C for 30 minutes to obtain a third suspension. The third suspension is filtered to obtain a cation containing only Li + a third lithium-rich solution;

[0075] (5) The third lithium-rich solution is evaporated and concentrated at 110° C., and after crystallization, it is washed with water at 100° C. to obtain high-purity nano lithium carbonate.

[0076] Example 2

[0077] This embodiment is basically the same as embodiment 1, the only difference being that in step (2), CaCO 3 Replaced by Ca(OH) 2 .

[0078] (2) At 60°C, add 6% Ca(OH) 2 , Ca(OH) 2The solution was added dropwise at a rate of 15 mL / min in the form of an emulsion. The addition was stopped when the pH value reached 5. The mixture was heated and stirred for 30 min to obtain a mixture of iron hydroxide precipitate and the second suspension.

[0079] Example 3

[0080] This embodiment is basically the same as embodiment 1, the only difference being that in step (2), CaCO 3 Replaced with CaO.

[0081] (2) At 60° C., 6.5% CaO by mass was added to the second lithium-rich solution. The CaO was added dropwise in the form of an emulsion at a rate of 15 mL / min. The addition was stopped when the pH value reached 5. The heating and stirring were continued for 30 min to obtain a mixture of iron hydroxide precipitate and the second suspension.

[0082] Example 4

[0083] This embodiment is basically the same as the embodiment 1, and the only difference is that the waste lithium iron phosphate LFP-1 is replaced by waste lithium iron phosphate LFP-2.

[0084] Example 5

[0085] This embodiment is basically the same as Embodiment 2, the only difference being that the waste lithium iron phosphate LFP-1 is replaced with waste lithium iron phosphate LFP-2.

[0086] Example 6

[0087] This embodiment is basically the same as Embodiment 3, with the only difference being that the waste lithium iron phosphate LFP-1 is replaced with waste lithium iron phosphate LFP-2.

[0088] like Figure 1 As shown, from left to right are SEM images of nano lithium carbonate prepared in Examples 1-3 of the present invention, Figure 2 As shown, from left to right are SEM images of nano lithium carbonate prepared in Examples 4-6 of the present invention. It can be seen from the figure that the nano lithium carbonate prepared by the method of the present invention is spherical petal-shaped.

[0089] like Figure 4 As shown, it is a schematic diagram of the main components of waste lithium iron phosphate LFP-1 and LFP-2. It can be seen from the figure that the main components of waste lithium iron phosphate LFP-1 and LFP-2 are Fe, P, Li, and Cu.

[0090] like Figure 5As shown, it is a comparison chart of the utilization rate of Li and the removal rate of Fe and Cu between Example 1 and Example 4. It can be seen from the figure that in the process of preparing nano lithium carbonate using waste lithium iron phosphate LFP-1 and LFP-2 in the present invention, the utilization rate of Li reaches more than 90%, and the removal rate of Fe and Cu basically reaches 100%, and the conversion rate and impurity removal performance are good.

[0091] like Figure 6 Shown are the XRD spectra of nano-lithium carbonate of Examples 1-6. The characteristic peaks of each spectrum prove that lithium carbonate is prepared in Examples 1-6.

[0092] like Figure 7 As shown, it is the infrared spectrum of the nano lithium carbonate of Example 1-6. It can be seen from the figure that the peak intensity of the lithium carbonate synthesized from the LFP-1 raw material is stronger than that of LFP-2. It can also be reflected from the original concentration of the raw materials. This is because the impurity element content of LFP-1 is less and the Li ion concentration is higher than that of LFP-2.

[0093] like Figure 8 As shown, it is a purity comparison chart of nano lithium carbonate of Examples 1-6. It can be seen from the figure that the purities of the nano lithium carbonate prepared in Examples 1-6 are 99.95%, 99.79%, 99.89%, 99.94%, 99.99% and 99.99%, respectively. Nano lithium carbonate with good purity can be prepared by the method of the present invention.

[0094] Comparative Examples 1-9

[0095] Comparative Examples 1-5 are substantially the same as Example 1, except that in step (1), the amount of sulfuric acid added was 100 mL, and no H 2 O 2 The sulfuric acid concentration was taken as a variable and was set to 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L and 1.0 mol / L respectively.

[0096] Comparative Examples 6-9 are substantially the same as Example 2, except that: in step (1), the concentration of sulfuric acid is changed, with the concentration of sulfuric acid being used as a variable, and the concentration of sulfuric acid is set to 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, and 0.8 mol / L, respectively.

[0097] The leaching rates of Li and Fe in the waste lithium iron phosphate LFP-1 of Example 1 and Comparative Examples 1-9 were measured. The results are shown in Fig. 9 .from Fig. 9 It can be seen that without adding H 2 O 2Under the conditions, the leaching rates of Li (black line in the figure) and Fe (red line in the figure) increased with the increase of sulfuric acid concentration. At this time, sulfuric acid leaching had no selectivity. The best leaching condition was 0.8 mol / L, with a Li leaching rate of 98.18% and a Fe leaching rate of 79.74%. 2 O 2 Under the conditions, the leaching rate of Fe decreased significantly with the increase of sulfuric acid concentration. At 0.6 mol / L, the leaching rate of Fe was only 21.46%. At the same time, the leaching rate of Li was 92.53% (compared with the case without adding H 2 O 2 The conditions are not much different), indicating that adding H 2 O 2 Under the conditions, the selectivity for lithium ions is good, and a large amount of iron remains in the leached residue. After roasting, FePO 4 This also verifies the good selectivity of leaching, which can not only increase the leaching rate of lithium ions accordingly, but also inhibit the entry of iron elements into the leachate.

[0098] Comparative Examples 10-17

[0099] Comparative Examples 10-13 are substantially the same as Example 1, except that in step (2), the pH value is used as a variable, and the addition is stopped when the pH value is set to 4, 4.5, 5.0, or 5.5, respectively.

[0100] Comparative Examples 14-17 are substantially the same as Example 2, except that in step (2), the pH value is used as a variable, and the addition is stopped when the pH value is 4, 6, 7, 8, or 9, respectively.

[0101] The utilization rate of Li and the removal rate of Fe in waste lithium iron phosphate LFP-1 were measured in Examples 1-2 and Comparative Examples 10-17. The results are shown in Fig.10 .like Fig.10 As shown in the left figure, when the calcification is calcium carbonate, as the pH value increases, the utilization rate of Li gradually decreases, while the removal rate of Fe gradually increases. In order to balance the utilization rate of Li and the removal rate of Fe, it is preferred to stop the dropwise addition when the pH value reaches 6; Fig.10 As shown in the figure (right), when the calcification is calcium hydroxide, the utilization rate of Li gradually decreases with the increase of pH value, while the removal rate of Fe is stable after the pH value reaches 5. In order to balance the utilization rate of Li and the removal rate of Fe, it is preferred to stop the dripping when the pH value reaches 5.

[0102] Comparative Examples 18-26

[0103] Comparative Examples 18-22 are substantially the same as Example 1, with the only difference being that in step (2), the heating stirring time is used as a variable, and the heating stirring time is set to stop at 5 min, 10 min, 15 min, 20 min, and 25 min, respectively.

[0104] Comparative Examples 23-26 are substantially the same as Example 2, with the only difference being that in step (2), the heating stirring time is used as a variable, and the heating stirring time is set to stop at 20 min, 40 min, 50 min, and 60 min, respectively.

[0105] Determine the concentration of Li and Fe in nano lithium carbonate of Examples 1-2 and Comparative Examples 18-26. The results are shown in Fig.11 .like Fig.11 As shown in the figure on the left, when the calcification is calcium carbonate, as the heating and stirring time increases, the concentration of Li in the nano-lithium carbonate remains basically stable, while the concentration of Fe gradually decreases, that is, the longer the heating time, the better the Fe removal rate; Fig.11 As shown in the figure (right), when the calcification is calcium hydroxide, as the heating and stirring time increases, the concentration of Li in the nano-lithium carbonate increases and then gradually stabilizes, while the concentration of Fe decreases and then gradually stabilizes. After heating and stirring for 30 minutes, the concentrations of Li and Fe are basically stable.

[0106] Comparative Examples 27-38

[0107] Comparative Examples 27-30 are basically the same as Example 1, with the only difference being that the reaction temperatures of step (1) and step (2) are changed, and the reaction temperature is used as a variable, and the reaction temperatures of step (1) and step (2) are set to 40°C, 50°C, 70°C, and 80°C, respectively.

[0108] Comparative Examples 31-34 are basically the same as Example 2, with the only difference being that the reaction temperatures of step (1) and step (2) are changed, and the reaction temperature is used as a variable, and the reaction temperatures of step (1) and step (2) are set to 20°C, 30°C, 40°C, and 50°C, respectively.

[0109] Comparative Examples 35-38 are basically the same as Example 3, with the only difference being that the reaction temperatures of step (1) and step (2) are changed, and the reaction temperature is used as a variable, and the reaction temperatures of step (1) and step (2) are set to 20°C, 30°C, 40°C, and 50°C, respectively.

[0110] The utilization rate of Li and the removal rate of Fe in waste lithium iron phosphate LFP-1 were measured in Examples 1-3 and Comparative Examples 27-38. The results are shown in Fig.12 .like Fig.12As shown in the figure on the left, when the calcification is calcium carbonate, as the reaction temperature increases, the utilization rate of Li remains basically stable, while the removal rate of Fe gradually increases and tends to be stable after 60°C; Fig.12 As shown in the middle figure, when the calcification product is calcium hydroxide, as the reaction temperature increases, the Fe removal rate gradually increases, and the Li utilization rate remains basically stable and has a downward trend at 60°C. Therefore, the reaction temperature is preferably within 60°C; Fig.12 As shown in the figure on the right, when the calcification is calcium oxide, as the reaction temperature increases, the Fe removal rate and Li utilization rate remain basically unchanged. Therefore, considering all factors, the preferred reaction temperature is 60°C.

[0111] Comparative Examples 39-51

[0112] Comparative Examples 39-44 are substantially the same as Example 1, except that in step (2), CaCO 3 The mass fraction of CaCO is set as a variable. 3 The mass fraction is 10%, 15%, 25%, 30%, 35% and 40%.

[0113] Comparative Examples 45-48 are substantially the same as Example 2, except that in step (2), CaCO 3 The mass fraction of Ca(OH)2 is taken as a variable, and the mass fraction of Ca(OH)2 is set to 2%, 4%, 8% and 10% respectively.

[0114] Comparative Examples 48-51 are substantially the same as Example 3, except that in step (2), CaCO 3 The mass fraction of CaO is taken as a variable, and the mass fraction of CaO is set to 5.5%, 6%, 7% and 7.5% respectively.

[0115] The utilization rate of Li and the removal rate of Fe in waste lithium iron phosphate LFP-1 were measured in Examples 1-3 and Comparative Examples 39-51. The results are shown in Fig.13 .like Fig.13 As shown in the left figure, when the calcification is calcium carbonate, as the mass fraction of calcium carbonate increases, the utilization rate of Li remains basically stable between 15-30%, and gradually decreases after 30%, while the removal rate of Fe gradually increases between 15-20%, and remains basically stable after 20%. Therefore, the preferred mass fraction of calcium carbonate in the present invention is 20-30%; Fig.13 As shown in (middle figure), when the calcification material is calcium hydroxide, as the mass fraction of calcium hydroxide increases, the utilization rate of Li and the removal rate of Fe both remain basically stable after 6%, and the utilization rate of Li has a downward trend after 10%. Therefore, the mass fraction of calcium hydroxide in the present invention is preferably 6-10%; Fig.13As shown in the figure (right), when the calcification is calcium oxide, as the mass fraction of calcium oxide increases, the utilization rate of Li and the removal rate of Fe remain basically stable after 6.5%. Therefore, the mass fraction of calcium oxide in the present invention is preferably greater than 6.5%.

[0116] The present invention collects the calcium carbonate waste residue from step (3) of Example 1 for recycling as an impurity remover, and tests its recycling effect. The results are shown in Fig.14 ,like Fig.14 As shown, the calcium carbonate waste residue can be recycled at least 4 times. During the 4 cycles, the utilization rate of Li and the removal rate of Fe can be maintained at more than 90%, and the pH value can be maintained at 6 after the calcium carbonate emulsion is added, ensuring the smooth progress of the reaction. In addition, the present invention also tests the XRD spectrum of the calcium carbonate waste residue after multiple cycles. The results are shown in Fig.15 ,from Fig.15 It can be seen that the calcium carbonate waste residue is still calcium carbonate after multiple cycles and can continue to be recycled.

[0117] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing nano lithium carbonate, characterized in that: The following steps are involved: (1) immersing waste lithium iron phosphate in a mixed solution of an acidic solution and an oxidant to obtain a first suspension, and performing solid-liquid separation on the first suspension to obtain a first lithium-rich solution; (2) adding a calcium compound to the first lithium-rich solution until the pH value is 6, continuing heating and stirring to obtain a mixture of iron hydroxide precipitate and a second suspension, and performing solid-liquid separation on the second suspension to obtain a second lithium-rich solution; (3) adjusting the pH of the second lithium-rich solution to 10-12, adding sodium carbonate, heating and stirring to obtain a third suspension, and performing solid-liquid separation on the third suspension to obtain a third lithium-rich solution; (4) Concentrating and washing the third lithium-rich solution to obtain nano lithium carbonate.

2. The method for preparing nano lithium carbonate according to claim 1, wherein The ratio of the waste lithium iron phosphate and the mixed solution in step (1) is (2-4) g:10 mL; The volume ratio of the acidic solution to the oxidant is (8-9):1, and the concentration of the acidic solution is 0.6-2 mol / L.

3. The preparation method of nano lithium carbonate according to claim 1, characterized in that, The acidic solution is a strong acid solution, including one or more of sulfuric acid, hydrochloric acid and nitric acid. The oxidant includes one or more of hydrogen peroxide, potassium permanganate and potassium dichromate.

4. The method for preparing nano lithium carbonate according to claim 1, wherein The immersion temperature in step (1) is 50-60° C., and the immersion time is 1-1.5 h.

5. The method for preparing nano lithium carbonate according to claim 1, characterized in that, The mass fraction of the calcification in step (2) is 6-30%; The calcified material includes one or more of calcium carbonate, calcium hydroxide and calcium oxide.

6. The method for preparing nano lithium carbonate according to claim 1, characterized in that: In step (2), after the second suspension is subjected to solid-liquid separation, calcium carbonate waste residue is obtained, and the calcium carbonate waste residue is recycled as a calcified product.

7. The method for preparing nano lithium carbonate according to claim 1, characterized in that: Step (2) is carried out at 50-60° C., and the heating and stirring time is 25-30 min.

8. The method for preparing nano lithium carbonate according to claim 1, wherein The heating and stirring in step (3) is performed at a temperature of 90-110° C. and for a time of 25-60 min.

9. The method for preparing nano lithium carbonate according to any one of claims 1 to 8, characterized in that: In step (3), the molar amount of calcium ions in the second lithium-rich solution is A, the molar amount of lithium ions in the second lithium-rich solution is B, and the amount of sodium carbonate added is C. A, B, and C satisfy the following condition: C=A+0.5B.

10. A nano lithium carbonate prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The nano lithium carbonate is in the shape of spherical petals.